Pengaruh Meal Experience Terhadap Customer Satisfaction di Yoshinoya Japanese Restaurant TSM Bandung - Daryanto Daryanto; Septy Indrianty; Apay Safari (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2022)
The purpose of this study was to determine how the effect of meal experience on customer satisfaction at Yoshinoya Japanese Restaurant TSM Bandung. This study uses quantitative methods with data collection techniques using literature study, observation, and distributing questionnaires with a descriptive and verification approach. The independent variable (X) in this study is meal experience which consists of several sub-dimensions, namely food and drink, variety in menu choice, level of service, price value for money, interior design, atmosphere and mood, location and accessibility, and food and beverage. beverage service employees and the dependent variable (Y) is customer satisfaction. Questionnaires were distributed to 112 consumers who visited and dined at Yoshinoya Japanese Restaurant TSM Bandung. The data analysis technique used is simple regression using the IBM SPSS for Mac 26.0 program. The results of the study based on the results of the meal experience variable has a significant influence with the coefficient of determination of 69.8% on customer satisfaction with a strong relationship. While the results of the partial test (t test) show that meal experience has a significant effect on customer satisfaction with a value of 15.963 because it is greater than the t table value of > 1.982. Thus, it is expected to increase the meal experience so that customer satisfaction increases.